Planning and management for rural development the PROPLAN/A approach, and its experiences in Colombia - Instituto Interamericano de Ciencias Agrícolas (IICA) (IICA, 2021)
64 p. pdf. Series Papers, conclusions and recommendations from technical events no. 264.